Beja Pedagogical Grammar - Wedekind, Klaus; Wedekind, Charlotte; Musa, Abuzeinab (Afrikanistik online, 2008)
Primarily, this book is for students who want to know Beja. In addition, it contains useful information for linguists who want to know about Beja.
Keywords: Afro-Asiatic; Afroasiatisch; Bedauye; Bedawiye; Bedja; Beja; Cushitic; Eritrea; Kuschitisch; Sudan; To-Bedawie